Overexpression of SIX1 is an independent prognostic marker in stage I–III colorectal cancer. Issue 9 (21st May 2015) - Kahlert, Christoph; Lerbs, Tristan; Pecqueux, Mathieu; Herpel, Esther; Hoffmeister, Michael; Jansen, Lina; Brenner, Hermann; Chang‐Claude, Jenny; Bläker, Hendrik; Kloor, Matthias; Roth, Wilfried; Pilarsky, Christian; et al.
<x xml:space="preserve">Abstract</x> Epithelial‐to‐mesenchymal transition (EMT) contributes significantly to tumor progression and metastasis. The assessment of EMT‐associated transcription factors could be a promising approach to identify biomarkers and potential therapeutic targets in colorectal cancer. In our study, we focused on the transcription factor "Sine oculis homeobox" (SIX) 1, which is a member of the superfamily of the homeobox genes and has been described to promote EMT in different types of tumors. Immunohistochemistry against SIX1 was performed on colorectal mucosa, adenomas, carcinomas‐in situ and primary adenocarcinomas. An expression score was developed and subsequently assessed for its prognostic value in two independent cohorts. Cohort 1 consisted of 128 patients with stage I–III colorectal cancer; cohort 2 included 817 patients with stage I–III colorectal cancer who had participated in the DACHS study. HCT‐116 cells were transfected with SIX1 plasmids and subjected to migration and colony formation assays. The expression of SIX1 increases gradually from mucosa to colorectal adenocarcinomas (p > 0.0001). Univariate and multivariate analyses reveal that high expression of SIX1 is associated with decreased overall survival (cohort 1: HR: 4.01, CI: 1.20–14.07, p = 0.025; cohort 2: HR: 1.43, CI: 1.014–2.02, p = 0.047). Overexpression of SIX1 induces a more mesenchymal‐like phenotype in HCT‐116 cells and enhances tumor migration. High expression of SIX1 is an independent prognostic marker in colorectal cancer. It might be a promising biomarker to stratify patients into different risk groups. Moreover, targeting SIX1 might be a novel therapeutic approach in patients with colorectal cancer.